MATHEMATICAL MODELING OF THE FOOD ITEMS IN THE GUT AND THEIR AVAILABILITY IN THE ENVIRONMENT FOR THE HILL-STREAM FISH, Barilius bendelisis (HAMILTON) BASED ON STRAUSS SELECTIVITY INDEX - MAMGAIN, DEEKSHA; RAYAL, RAJESH; DOBRIYAL, A. K.; BAHUGUNA, PANKAJ (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
Barilius bendelisis (Hamilton) is an ornamental fish. The feeding ethos of fish is of great concern for its culture and breeding. Strauss selectivity index is simply the unweighted difference in proportion (L= ri - pi) of the prey item in the gut and the environment. It ranges from -1 to + 1 with a positive value indicating preference and the negative value indicating avoidance or inaccessibility. Three length-groups (1 < 5cm, 5-10cm. and > 10cm.) were analyses in current study. Barilius bendelisis has been found to accompany a change of food habit with more emphasis on insect items in higher length groups. It had been noticed that in Barilius bendelisis feeding ethos showed dipterans larva as more available digestible food part in gut portion than ephemeroptera and trichoptera larvae in all different size groups.